Análise comparativa do comportamento mecânico dos instrumentos rotatórios de NiTi Profile Vortex, Race e proTaper Universal - Juliano de Lima Alves (2011)
The mechanical properties of endodontic instruments are important parameters for the safe and efficient clinical use in endodontic practice. The aim of this study was to evaluate the geometric characteristics, the structural, physical, chemical and mechanical properties of NiTi endodontic instruments ProFile Vortex, RaCe and ProTaper Universal. The chemical components have all been analyzed with X-Ray energy spectroscopy, the present phases determined by X-Ray diffractions, the transformation temperatures obtained with differential scanning calorimeter and the topographic features were evaluated by scanning electron microscopy. The geometric and dimensional characteristics, especially the area and diameter 3 mm from the tip were analyzed using the ImagePro Plus 6.0 software. The mechanical behavior was evaluated by bending and torsion tests, as specified by ISO 3630-1, and flexural fatigue test until fracture. Data were analyzed by ANOVA with a confidence level of 95%. The instruments Vortex, RaCe and ProTaper Universal showed similar chemical composition and -phase as the main constituent at room temperature. However, the average values of transformation temperatures of the instrument Vortex were significantly higher than other rotary systems tested. The Vortex instruments were significantly more flexible, possibly due to thermomechanical treatments they have undergone during manufacture. Instruments Vortex 25/.06 showed peak torque significantly higher than those of RaCe 25/.06 and ProTaper F1. However, in the group with the highest caliber, ProTaper F2 instrument showed the statistically most torsional resistance. In the fatigue tests, Vortex system showed a significantly higher fatigue life than the other instruments examined. Whereas instruments have similar diameters and geometry, the thermomechanical treatment performed in the M-Wire wire used in producing the Vortex system, represented an important improvement in the mechanical properties of the instruments, when compared with rotary systems manufactured with conventional NiTi wires.